FREQUENCY OF Toxoplasma gondii AND Neospora caninum IN VICUÑAS (Vicugna vicugna) OF THE PERUVIAN CENTRAL SIERRA BY THE IMMUNOFLUORESCENCE INDIRECT (IFI) AND INDIRECT ELISA TECHNIQUES - Pinedo R., Karen (2014)
The objective of this study was to estimate the frequency of antibodies againstToxoplasma gondii and Neospora caninum in vicuñas in the Yauli province, Junín, Peru,and to determine the degree of concordance between the indirect immunofluorescence(IFA) and indirect ELISA test. A total of 79 blood samples were obtained during a «Chaku»(rodeo). The results showed a frequency of antibodies against T. gondii of 5.1 and 3.1%for indirect ELISA and IFA respectively, whereas none of the samples were positive to N. caninum. The kappa value was 0.85, but the small number of positive samples does notallowed inferring that the degree of concordance between the two test was good.